Analisis Penerapan Sistem Manajemen Mutu ISO 9001:2015 Terhadap Kinerja Operasional Perusahaan - Yurnalisdel Yurnalisdel; Isdaryanto Iskandar (Publikasi Indonesia, 2022)
In the era of global competition, the quality of products owned by companies needs to be evaluated because of an increase in consumer awareness of the quality of products produced by companies. Currently, the ISO 9001:2015 standard has been used by many organizations ranging from small, medium to large all over the world. Several empirical literature studies that have been carried out explain the importance of quality management standards in optimizing continuous improvement of the company's operational performance, where the aim is to meet the needs and expectations of customers in the market. Although the ISO 9001: 2015 standard is useful for companies, there is no agreement between practitioners and scholars whether the ISO 9001: 2015 standard makes it possible to improve the company's operational performance. Therefore, this research is aimed at reviewing and testing a hypothesis, namely the relationship between ISO 9001:2015 quality standards and different perspectives on company operational performance in order to find out the role of ISO 9001:2015 standards in increasing a company's operational performance. This research was conducted in order to be able to identify and observe empirical literature studies that are relevant to the present. The results of the empirical studies that have been conducted found that ISO 9001:2015 has a significant influence on internal business processes, has a positive correlation with indicators of innovation and learning at a significant level and ISO 9001:2015 standards are recommended so that they can be used in improving the company's operational performance.